Legal Analysis of Children as Victims of Sexual Violence - Rini Angriani; Syawal Abdulajid; Suwarti Suwarti (Syntax Corporation Indonesia, 2023)
This study aims to analyze the factors that cause children to become victims of sexual violence committed by perpetrators of crimes and obstacles in providing legal protection for children as victims of sexual violence. The applied research method is normative legal research, leading to the identification of legal rules, principles, and doctrines in response to the legal problems faced. The scientific approach in this study is based on the disciplines and working principles of normative legal science, focusing on the analysis of law itself. The results of this study show that legal protection measures provided for victims of underage sexual relations and rape in the criminal justice system are carried out through preventive and repressive approaches, both by the community and the government (through law enforcement officials), such as providing protection/supervision from various threats that can endanger the lives of victims, providing adequate medical and legal assistance, examination and judicial process. This research has significant implications in identifying the triggering factors of sexual violence against children and challenges in their legal protection. The normative legal research approach not only provides insight into relevant legal aspects, but also explores legal principles and doctrines to formulate solutions to these problems.